Nisa’ Exclusive / Wan Nur Sabrina Wan Saifuddin … [et al.] - Wan Saifuddin, Wan Nur Sabrina; Abd Kahar, Nur Izayu Syafiqah; Mad Yasir, Nurul Farzana; Shariful Izam, Nur Amirah Basyirah (Faculty of Business and Management, 2020)
Our company, Nisa’ Exclusive is being operated since 3rd February 2020 at Bandar Baru Bangi, Selangor. The place located was strategic and it is easily to find. Our business creates an innovation of prayer mat which is a Seat table Prayer Mat. Our objective is to makes our Muslims perform their obligation of solat, reading al-Quran comfortably. This new creation of the Seat table Prayer Mat is mainly to support our back to lean especially for those who have back pain and legs problem. We ensure that our Seat table Prayer Mat gives more comfortable position to our Muslim when they want to seat and reading al-Quran or to listen or hear a tazkirah. It also can be used at anytime and anywhere because we also provide a bag so the Seat table Prayer Mat can be keep and carry easily. Also, it can be purchase in walk-in store or in our website. The purpose of preparing Business Model Canvas (BMC) is to clearly gives the idea and details of the product, to go through the process of our business, to detect the strengths and weaknesses. Key partners and activities is important to create alliances with partners and having a good knowledge of the core of activities. Meanwhile, a key resource is needed to perform in terms as physical or human resources. The value proposition is about the core of the company. It is also important to create a relationship with a customers and how to organizationally to distribute the product among the customers. Identifying the needs in the customer segments will lead a customer satisfaction. The cost structure can determine the amount of variable cost, profit and even the turnover. The revenue streams provide a clear insight into the revenue model.